The March 2023 Bank Interventions in Long-Run Context – Silicon Valley Bank and beyond - Metrick, Andrew,Schmelzing, Paul (National Bureau of Economic Research, 2023)
U.S. and European banking institutions were hit by a wave of distress in March 2023. Policymakers on both sides of the Atlantic reacted with an array of interventions, some targeting individual institutions, others designed to shore up the banking sector as a whole. This paper contextualizes events using a new long-run database on banking-sector policy interventions over the last eight centuries. On that basis, recent actions have already been unusual in their policy mix and size - in the database, the vast majority of events with the same pattern of interventions ultimately evolved into
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Bank; Bankenkrise; Finanzkrise; Bankenregulierung; USA; Financial Crises